THE EFFECT OF CHEMICAL AND MICROWAVE HEATING TREATMENT FOR REDUCING SUGAR RECOVERY - Yulia Tri Rahkadima; Medya Ayunda Fitri (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2022)
Microwave heating treatment was the one type of pretreatment process used in the manufacture bioethanol because it can be applied singly or in combination with other chemicals. The purpose of this study was to determine the effect of microwave heating on the pretreatment process using acid and alkaline solvents. The research was carried out in two stages, namely the preparation of raw materials and pretreatment with microwave. At the stage of preparation of raw materials, bagasse was dried for 2 days and then crushed to a size of 50 mesh to uniform the size of the raw materials. The raw materials that have been prepared are then subjected to a pretreatment process. The pretreatment process was carried out using a modified microwave with temperature settings and the addition of a stirrer. 5 grams of bagasse powder and 200 ml of a solution of H2SO4 or NaOH (0.2 M, 0.4 M, and 1 M) were put into a round tool flask and then put into the microwave. Pretreatment was carried out at 180°C with time variables of 10, 15, 20, 25, and 30 minutes. Then the solution was separated from the residual solid by filtration and the solution was neutralized with 1 M HCl. The results showed that the use of acidic and alkaline solvents, high concentrations of solvents can lead to smaller the acquisition of reducing sugars in the liquid product phase. The highest percentage of reducing sugar obtained is 0.559% when using an acid solvent with a concentration of 0.1 M for 20 minutes.